Penentuan Jenis Tanah untuk Menghasilkan Genteng Berkualitas Menggunakan Fuzzy ELECTRE - Mufarrohah, Mufarrohah; Yulianto, Tony; Faisol, Faisol (Zeta - Math Journal, 2020)
Soil is the layer of the earth's surface that comes from parent material which has undergone an advanced process. In the past, roof tiles came from clay that was molded and heated to dry. Therefore, for selecting quality tile, it must be in accordance with the specified soil. Some of the soils that have been selected from tile making are clay clay, red soil, black soil, brown soil (kobih), yellow soil (kombung). while good soil is of course land that can meet the maker of his needs. Some of the criteria for good and quality tile, for example in terms of strength, precision, non-cracking, and yellow ivory. The decision support system is a method designed to assist users in making decisions and can also be used as a quality tile selection recommendation system for makers. This decision support system uses the Fuzzy ELETRE method as a process in determining the best soil type so that the results show that TA (combination of clay, brown (kobih), black) and TC (combination of clay, yellow, black) dominates more than TB (combination). loam, red, black).